2021
DOI: 10.1007/s12144-021-02003-z
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as a mediator and moderator in the relationship between adverse childhood experiences and depression

Abstract: Adverse childhood experiences (ACEs) have been associated with a variety of negative physical and psychological health outcomes. The mechanisms by which this occurs and potential protective factors present in this relationship are understudied. Mindfulness is a cognitive resource that may protect individuals against symptoms of psychological distress. It has five core facets and encourages a nonjudgmental acceptance of the present moment. The purpose of this study was to explore the role of mindfulness in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…In essence, mindfulness has been found to be a protective factor against negative work and health outcomes. Yet, a smaller body of evidence has begun to show that mindfulness may have a dual mediator/moderator role in the relation between stressors and health outcomes [ 73 , 74 ]. Taken together, the literature on mindfulness, particularly in the context of the JD-R model, has already shown the moderating effect of mindfulness.…”
Section: Literature Review Theory and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, mindfulness has been found to be a protective factor against negative work and health outcomes. Yet, a smaller body of evidence has begun to show that mindfulness may have a dual mediator/moderator role in the relation between stressors and health outcomes [ 73 , 74 ]. Taken together, the literature on mindfulness, particularly in the context of the JD-R model, has already shown the moderating effect of mindfulness.…”
Section: Literature Review Theory and Conceptual Frameworkmentioning
confidence: 99%
“…Based on JD-R theory and mindfulness frameworks [ 39 , 40 , 41 , 42 , 55 , 73 ], a conceptual model involving JD-R, state mindfulness, and burnout is proposed, as shown in Figure 1 , to examine the mediational pathway between JD-R and burnout. This conceptual model posits that stressors such as JD may affect an individual’s moment-to-moment, or state, mindfulness by impairing their ability to stay aware of the immediate environment and/or to stay non-judgmental.…”
Section: Literature Review Theory and Conceptual Frameworkmentioning
confidence: 99%
“…Zimmer-Gembeck et al (2021) found that adolescents with higher dispositional mindfulness would have lesser mental issues. The research about American university students reports that mindfulness can regulate the effect of adverse childhood experiences on depression (Mckeen et al, 2021). At the same time, paying attention to children's feelings and accepting children without evaluation can reduce their depression through self-esteem improvement (Hu & Ai, 2016).…”
Section: Mindfulness As a Moderatormentioning
confidence: 99%
“…For example, some scholars have found that positive childhood experiences at home and school protect at-risk adolescents against mental health problems [ 22 ]. Mindfulness is a cognitive resource that protects people against symptoms of psychological distress [ 23 ]. Self-esteem mediates the negative correlation between child maltreatment and depressive symptoms and protects against the adverse effects of early adversity exposure on mental health [ 24 ].…”
Section: Introductionmentioning
confidence: 99%